The effect of contemporary nursing care programme on Islamic work ethics and nursing caring behaviour in Southern Thailand - Pairoh, Hasanah (2021)
Issues related to quality of nursing care are still being debated in the literature while only a few studies were documented focusing on nursing caring behaviour in Southern Thailand. Non-caring behaviours were found to make the patients feel less confident and not empowered. This study aimed at examining the effect of the Contemporary Nursing Care Programme on nursing caring behaviour and work ethics. A quasi-experimental, pre-test and post-test design was implemented among 60 nurses who worked at Channae Hospital (experimental group, n=30) and Bachok Hospital (control group, n=30). The module of Contemporary Nursing Care Programme which was developed based on the human care conceptual model consisted of intention, utilizing professional knowledge skill, effective communication and respect domains. The experimental group received five sessions of Contemporary Nursing Care Programme and prior to that, both the experimental and control group received a pre-test while the post-test was conducted in the following week after completion of the programme. The Thai Nursing Caring Behaviour Scale (TNCBS) and Islamic Work Ethics (IWE) were used to measure nursing caring behaviour and work ethics and analysed using SPSS software. To further understand the two variables, a semi-structured interview was conducted among selected respondents (n=10). The results of paired t-tests showed nursing caring behaviour and work ethics were improved (p < .05) after the programme. Semi-structured interview which was analysed using thematic analysis revealed themes such as standard of care, role of nurses, and holistic care. The study found that the Contemporary Nursing Care Programme was useful in promoting caring behaviour and work ethics among nurses. Thus, the Contemporary Nursing Care Programme should gradually be implemented in the hospital setting particularly among new nurses. It is recommended that future research should implement a programme or training that embraces diverse culture and belief in order to achieve holistic care.